M#1045: Training Course in Focused Assessment with Sonography for HIV/TB in HIV Prevalent Medical Centers in Malawi - Canan, Timothy (J Glob Radiol, 2018)
PURPOSE: Training medical providers of different backgrounds the “focused assessment with sonography for HIV-associated TB” (FASH) exam to expand the availability of ultrasound for TB diagnosis in resource poor settings in the central region of Malawi. METHODS AND MATERIALS: A survey was completed by the 19 eligible participants before and after a 4-day training course regarding the utility of the FASH exam. A six-question quiz was used to assess knowledge of the use of ultrasound in the FASH exam before and after the course. RESULTS: Participants’ knowledge of the FASH technique significantly improved after the four-day course with a 32% increase in total quiz questions answered correctly (p<0.001). Ninety-five percent (n= 18) of participants answered that they would “likely” incorporate FASH in their clinical practice. Furthermore, 100% (n=19) of participants agreed that the FASH exam would improve their ability to diagnose TB and 95% (n=18) agreed that FASH would improve patient care in their clinic. CONCLUSIONS: After completing a 4-day training course, medical providers were more knowledgeable about the FASH exam and its findings, and felt more comfortable using ultrasound for the diagnosis of TB. Participants were also unanimous in opinion that the FASH ultrasound exam would improve their ability to diagnose TB.